Planimetry of aortic valve area using multiplane transoesophageal echocardiography is not a reliable method for assessing severity of aortic stenosis. - Bernard, Y. (1997)
OBJECTIVE: To assess the reliability of aortic valve area planimetry by multiplane transoesophageal echocardiography (TOE) in aortic stenosis. DESIGN: Study of the diagnostic value of aortic valve area planimetry using multiplane TOE, compared with catheterisation and the continuity equation, both being considered as criterion standards. SETTING: University hospital. PATIENTS: 49 consecutive patients (29 male, 20 female, aged 44 to 82 years, average 66.6 (SD 8.5)), referred for haemodynamic evaluation of an aortic stenosis, were enrolled in a prospective study. From this sample, 37 patients were eligible for the final analysis. METHODS: Transthoracic and multiplane transoesophageal echocardiograms were performed within 24 hours before catheterisation. At transthoracic echo, aortic valve area was calculated by the continuity equation. At TOE, the image of the aortic valve opening was obtained with a 30-65 degrees rotation of the transducer. Numerical dynamic images were stored on optical discs for off-line analysis and were reviewed by two blinded observers. Catheterisation was performed in all cases and aortic valve area was calculated by the Gorlin formula. RESULTS: Feasibility of the method was 92% (48/52). The agreement between aortic valve area measured at TOE (mean 0.88 (SD 0.35) cm2) and at catheterisation (0.79 (0.24) cm2) was very poor. The same discrepancies were found between TOE and the continuity equation (0.72 (0.26) cm2). TOE planimetry overestimated aortic valve area determined by the two other methods. Predictive positive and negative values of planimetry to detect aortic valve area < 0.75 cm2 were 62% (10/16) and 43% (9/21) respectively. CONCLUSIONS: Planimetry of aortic valve area by TOE is difficult and less accurate than the continuity equation for assessing the severity of aortic stenosis.